Experimental Investigation on the Energy Consumption Difference between the Dynamic Impact and the Drilling Tests of Rocks - Shoudong Xie; Mingjian Huang; Junji Lu; Wang Xi; Zhenyang Xu (Shock and Vibration)
The split Hopkinson pressure bar (SHPB) technique and various drilling tests were performed on three types of lithologies (granite and cyan and red sandstone) to understand the variation in energy consumption (EC) of the different methods used for rock crushing. The dynamic behavior of rocks was analyzed based on the dynamic stress-strain curve, the peak stress, the energy, and the failure mode for the SHPB test, while the drilling curve, the influence of the drilling pressure (DP) and the revolution speed (RS) on the drilling speed (DS) were analyzed for the drilling test. Additionally, the EC difference was compared based on the EC required to break a single unit volume of rock. The obtained results indicate that the sensitivity of the dynamic strength of rocks with different lithologies to strain rate is different and that the higher the uniaxial compressive strength is, the more sensitive it is. Additionally, the strengthening of the peak stress is more pronounced with the increase in the strain rate. The energy utilization efficiency (EUE) of the SHPB test sample has a positive correlation with the strain rate. Moreover, the typical drilling process can be divided into the initial drilling and stable drilling stages, with the DS during the stable drilling stage being lower than that during the initial drilling stage. The DP and the RS have a linear positive correlation with the DS, with the influence of the DP on the DS being more obvious. Finally, the EC during the drilling process is higher than the EC during the SHPB technique.